2015
DOI: 10.4012/dmj.2014-185
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of commonly used luting cements —An <i>in vitro</i> study

Abstract: The study aimed to 1) evaluate the cytotoxicity of luting cements: Hoffmann's Zinc Phosphate (Hoffmann's ZP), GC Fuji Plus Resin Modified Glass Ionomer (Fuji Plus RMGI) and 3M ESPE RelyX Unicem Resin Cement (RelyX Unicem RC) and 2) test if pre-washing reduces the cements' cytotoxicity. In vitro human gingival fibroblast (HGF) culture model was chosen. The cytotoxicity was evaluated by MTT test, the cell viability -by staining the cells with AO/EB dye mixture. The means±SD of Cell Survival Ratio (CSR%) were com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 32 publications
(50 reference statements)
1
13
1
Order By: Relevance
“…Our result about higher level of AO effect by HPMV method of Ketac Cem (Glass Ionomer Cement) regarding Zn-phosphate and polycarboxylate has no explanation. If speculate that AO capacity is inverse correlation to the cytotoxicity level, the results of Trumpaite-V 16 where Zn-phosphate exposed as lower cytotoxic then Fuji Plus RMGIC, are in discrepancy to the ours. Unfortunately, our results of AO capacity are not comparable to the results of other studies due to the difference in laboratory methodologies and sample preparation.…”
Section: Discussioncontrasting
confidence: 85%
“…Our result about higher level of AO effect by HPMV method of Ketac Cem (Glass Ionomer Cement) regarding Zn-phosphate and polycarboxylate has no explanation. If speculate that AO capacity is inverse correlation to the cytotoxicity level, the results of Trumpaite-V 16 where Zn-phosphate exposed as lower cytotoxic then Fuji Plus RMGIC, are in discrepancy to the ours. Unfortunately, our results of AO capacity are not comparable to the results of other studies due to the difference in laboratory methodologies and sample preparation.…”
Section: Discussioncontrasting
confidence: 85%
“…It had been founded that released resin monomers cause chemical damage to cells [25]. Trumpaite-Vanagiene et al studied the cytotoxicity of 3 luting cements and concluded that luting cements may have a cytotoxic potential [26]. The reduction of curing time significantly enhances the cytotoxicity of luting resin cement, and adequate conversion of monomers into polymers can reduce cytotoxicity of resin cement [27].…”
Section: Introductionmentioning
confidence: 99%
“…One year after AR Five years after AR A relatively high number of respondents do not apply modern methods for obturation of the root canal system before apical resection. There are still dentists who use zinc phosphate cement for root canal filling although it's with high cytotoxity (11,12). It is noteworthy that the application of this material is characteristic of dentists with over 30 years of experience.…”
Section: Discussionmentioning
confidence: 99%